Struktur Komunitas Mikroartropoda Tanah di Lahan Pertanian Organik dan Anorganik di Desa Batur Kecamatan Getasan Salatiga - Husna, Shifa Aulia; Hadi, Mochamad; Rahadian, Rully (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Soil microarthropods is a arthropods that have an important role in decomposing organic materials and soil nutrients. On the farmland there is organic materials content and soil nutrients that abundants enough, because the addition of manure as a source of energy in the ground. The research was conducted in August-October 2015 took place in the field of organic and inorganic farmland in the Batur Village, Getasan Sub-district, Salatiga. This study aimed to examine the soil microarthropods community structure in organic and inorganic farmland as well as the effect of chemical and physical environmental factors to community structure of soil microarthropods. The study was conducted with samples of soil sampling method (PCT) and extracted using Barlese Funnel Extractor. Statistically show that diversity of soil microarthropods between organic and inorganic farmland are not significantly different. There is found 28 taxa of soil microarthropods in organic farmland and 23 taxa in inorganic. The highest total individual density of the taxa are exist in the organic farmland (2260 individual/ mÂ²). The highest abundance of soil microarthropods taxa in inorganic farmland are Carabidae (26,55%) dan Prostigmata (13,27%), while in inorganic farmland are Carabidae (17,24%) dan larva Coleoptera (13,79%). The evenness of soil microarthropods taxa in organic farmland are much low compared with inorganicfarmland, because there is a dominant taxa (Carabidae). There is an influence relation between the chemical and physical environmental factors including water content, porosity, nutrient, and organic materials with community structure of soil microarthropods.Â Key words:Community structure, Soil microarthropods, Organic and inorganic farmland